Does low-field dedicated extremity MRI (E-MRI) reliably detect bone erosions in rheumatoid arthritis? A comparison of two different E-MRI units and conventional radiography with high-resolution CT scanning. Issue 8 (21st August 2008) - Duer-Jensen, A; Ejbjerg, B; Albrecht-Beste, E; Vestergaard, A; Døhn, U Møller; Hetland, M Lund; Østergaard, M
Abstract : Objectives: To compare the ability of two different E-MRI units and conventional radiography (CR) to identify bone erosions in rheumatoid arthritis (RA) metacarpophalangeal (MCP) and wrist joints with CT scanning as the standard reference method. Methods: 20 patients with RA and 5 controls underwent CR, CT and two E-MRI examinations (Esaote Biomedica Artoscan and MagneVu MV1000) of one hand during a 2-week period. In all modalities, each bone of the wrist and MCP joints was blindly evaluated for erosions. MagneVu images were also assessed for the proportion of each bone being visualised. Results: 550 bones were examined. CT, Artoscan, MagneVu and CR detected 188, 116, 55 and 45 bones with erosions, respectively. The majority were located in the carpal bones. The sensitivity of the Artoscan for detecting erosions was higher than that of the MagneVu and CR (MCP joints: 0.68, 0.54 and 0.57, respectively; wrists: 0.50, 0.23 and 0.29). Corresponding specificities for detecting erosions were 0.94, 0.93 and 0.99, respectively, in the MCP joints and 0.92, 0.98 and 0.98 in the wrist. The MagneVu allowed visualisation of 1.5 cm of the ventral-dorsal diameter of the bone. In the wrist, 31.6% of bones were visualised entirely and 37.9% of bones were 67–99% visualised. In MCP joints, 84.2% of bones were visualised entirely and 15.8% of bones were 67–99% visualised. Conclusion: With CT as the reference method for detecting erosions in RA hands, the Artoscan showed higher sensitivity than the MagneVu and CR. All imaging modalities had high specificities. The better performance of the Artoscan should be considered when selecting an imaging method in RA.